Concordance between childhood injury diagnoses from two sources: an injury surveillance system and a physician billing claims database. Issue 3 (2nd June 2005) - Kostylova, A; Swaine, B; Feldman, D
Abstract : Objectives: (1) To determine the concordance between injury diagnoses (head injury (HI), probable HI, or orthopedic injury) for children visiting an emergency department for an injury using two data sources: an injury surveillance system (Canadian Hospitals Injury Research and Prevention Program, CHIRPP) and a physician billing claims database (Régie de l'assurance maladie de Québec, RAMQ), and (2) to determine the sensitivity and specificity of diagnostic and procedure codes in billing claims for identifying HI and orthopedic injury among children. Design: In this cross sectional cohort, data for 3049 children who sought care for an injury (2000–01) were obtained from both sources and linked using the child's personal health insurance number. Methods: The physician recorded diagnostic codes from CHIRPP were used to categorize the children into three groups (HI, probable HI, and orthopedic), while an algorithm, using ICD-9-CM diagnostic and procedures codes from the RAMQ, was used to classify children into the same three groups. Results: Concordance between the data sources was "substantial" (weighted Kappa 0.66; 95% CI 0.63 to 0.69). The sensitivity of diagnostic and procedure codes in the RAMQ database for identifying HI and for orthopedic injury were 0.61 (95% CI 0.57 to 0.64) and 0.97 (95% CI 0.96 to 0.98), respectively. The specificity for identifying HI and for orthopedic injury were 0.97 (95% CI 0.96 to 0.98) and 0.58 (95% CI 0.56 to 0.63), respectively. Conclusion: Combining diagnostic and procedures codes in a physician billing claims database (the RAMQ database) may be a valid method of estimating injury occurrence among children.